(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The main tasks solved in the design, construction and operation of power supply systems for industrial enterprises are to optimize the parameters of these systems by choosing the right range of parameters. The reliability of the electrical system and its individual components largely depends on how correctly and fully the dangerous manifestations of the modes arising in it are taken into account, which can be caused both accidentally and intentionally. Their knowledge is necessary, first of all, to prevent the emergence of dangerous regimes and to develop measures to combat their harmful consequences.